CRISPR/Cas12a-based method coupled with isothermal amplification to identify Alternaria spp. isolated from wheat grain samples - Shaizadinova, Aisha; Amanzholova, Meruyert; Rukavitsina, Irina; Abeldenov, Sailau; Zhumakayev, Anuar Rysbekovich (Frontiers in Microbiology, 2025)
Alternaria fungal species are considered major plant pathogens, infecting various crops and resulting in significant agricultural losses. Additionally, these species can contaminate grain with multiple mycotoxins that are harmful to humans and animals. Efficient pest management relies on timely detection and identification of phytopathogens in plant and grain samples, facilitating prompt selection of a crop protection strategy. Conventional identification tools, such as morphological characterization and identification based on polymerase chain reaction (PCR)-based methods, are time-consuming and laboratory-bound, limiting their implementation for on-site diagnostics essential in the agricultural industry. Isothermal amplification methods, including nucleic acid sequence-based amplification (NASBA), loop-mediated isothermal amplification (LAMP), and recombinase polymerase amplification (RPA), enable nucleic acid amplification at constant temperatures, making them ideal for point-of-care diagnostics without the need for thermal cycling equipment. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 12a (Cas12a)-based identification, coupled with such isothermal amplification methods, represents an emerging nucleic acid-based technology for detecting plant pathogens at high accuracy and sensitivity. This study aimed to develop a CRISPR/Cas12a-based method integrated with RPA amplification for specific detection of Alternaria spp. isolated from wheat grain samples. The developed method targeted the β-tubulin gene was successfully identified Alternaria strains within a 20-min RPA amplification followed by a 30-min CRISPR/Cas12a reaction and visualization of results. Specificity test included pathogenic fungal species commonly hosted wheat grain, such as Fusarium spp. Bipolaris sorokiniana, and Nigrospora oryzae revealed high specificity of the method for Alternaria species. Furthermore, the method exhibited high sensitivity, detecting Alternaria DNA down to 100 copies, validated by real-time fluorescence readout. A fluorescence assay was employed to visualize the results of RPA and CRISPR/Cas12a reaction, demonstrating substantial implementation potential of the method in point-of-care detection of Alternaria spp. In conclusion, we present the CRISPR/Cas12a-based method as a potentially sustainable approach for the rapid, precise, and specific nucleic-acid-based identification of Alternaria species in grain samples.